Integrating the Biopsychosocial Model to Address the Complex Needs of Perimenopausal Women: A Comprehensive Framework - ANITHA G; Dr. VASANTHA S (The Bioscan, 2024)
Perimenopause, the transitional phase leading to menopause, is a period marked by significant biological, psychological and social changes. The symptoms and challenges experienced during this stage can be complex and varied, affecting a woman's physical health, emotional well-being, and social dynamics. The Biopsychosocial Model offers a comprehensive framework for addressing these multifaceted needs by integrating biological, psychological, and social factors in healthcare. This model recognizes the importance of not only managing physical symptoms such as hot flashes, sleep disturbances, and hormonal imbalances, but also addressing the psychological challenges, including mood disorders and cognitive changes, as well as the social pressures women face regarding aging, care giving responsibilities, and workplace demands. By adopting a holistic approach that considers all these dimensions, healthcare providers can offer more personalized, effective interventions. This paper explores how the Biopsychosocial Model can be applied to the care of perimenopausal women, emphasizing the need for integrated, interdisciplinary approaches that include medical treatment, psychological support and social resources to improve overall quality of life during this transition.